1994
DOI: 10.1007/bf02211807
|View full text |Cite
|
Sign up to set email alerts
|

Direct intraperitoneal insemination and controlled ovarian hyperstimulation in subfertile couples

Abstract: The pregnancy rate was 33.3% for all couples and 15.0% for all cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…DIPI can be chosen as a first line treatment in patients with unsolved or recurrent isthmic stenosis where tubal patency has been confirmed, no intrauteriune contour defects exist, and there is no profound male factor infertility [8-10]. Previous randomized study comparing pregnancy rates after IPI and standard IUI showed roughly equivalent outcomes [10].…”
Section: Discussionmentioning
confidence: 99%
“…DIPI can be chosen as a first line treatment in patients with unsolved or recurrent isthmic stenosis where tubal patency has been confirmed, no intrauteriune contour defects exist, and there is no profound male factor infertility [8-10]. Previous randomized study comparing pregnancy rates after IPI and standard IUI showed roughly equivalent outcomes [10].…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal insemination (IPI) warrants consideration in such cases of cervical stenosis where tubal patency has been confirmed, no intrauteriune contour defects exist, and there is no profound male factor infertility diagnosis [11-13]. As with the more commonly performed IUI, the efficacy of IPI is directly related to the overall spermatozoa concentration, motility, and morphology [14,15].…”
Section: Discussionmentioning
confidence: 99%